/Effect of the Activation Technique and the Different Interactions of Several Irrigation Solutions on Dental Discoloration and Microcracks in Dentinal Walls after Canal Shaping (In Vitro- Study)/ (Journal of Hama University, 2022)
The aim of this In Vitro study was to evaluate the effect of two  Activation Techniques and the Interactions of Several Irrigation Solutions on Dental Discoloration and Microcracks in Dentinal Walls after Canal Shaping.one hundred extracted Single Root and Canal Tooth and  free of caries or Cracks were used,and divided into 10 Groups according to Irrigation Solution or Solutions and Activation Technique :Group I (Negative Control group):irrigation with Saline only, Group II(Positive Control group):irrigation with CHX  only(activated with PUI), Group III:irrigation with NaOCL only(activated with PUI), Group IV:irrigation with NaOCL and EDTA(activated with PUI),Group V:irrigation with NaOCL and H2O2(activated with PUI), Group VI:irrigation with NaOCL and CHX(activated with PUI),Group VII:irrigation with NaOCL only(activated with laser),Group VIII:irrigation with NaOCL and EDTA(activated with laser),Group IX:irrigation with NaOCLand H2O2(activated with laser),Group X:irrigation with NaOCL and CHX(actived with laser).The Color of dental crowns and Roots was recorded As a baseline before starting working using Vita Easyshade V. Access Cavities,working Length determining,root canal preparing using SOCO files and irrigation were done according to each group then The color was recorded after one day, a week and two weeks, then The root cross sections were done away 3,6,9mm from the apex and Examined under microscopic magnification to investingate the number and extent of cracks .ANOVA test was used to show the nature of difference of the discoloration and microcracks of studied groups.The results shows  statistically significant differences between II,VI, X and the other groups In term of discoloration ,and statistically significant differences between all groups and the negative control group and No statistically significant differences Among groups  regarding to microcracks. Conclusion: Use of CHX alone or Post-NaOCL cause important Dental discoloration whether activated with PUI or laser and All solutions and the activation techniques used in our search, caues microcracks similar relatively. Clinical significance: Chlorhexidine should not used alone or Post-NaOCL because result in they dental discoloration
Keywords: Discoloration, Microcracks, Sodium hypochlorite ,EDTA, Hydrogen Peroxide ,Chlorhexidine , PUI ,Laser